The Influence of Safety Communication on Safety Culture and Operational Excellence in High-Risk Industries - Arief Zulkarnain; Puji Lestari; Kholil Kholil (Eduvest - Journal of Universal Studies, 2025)
Industrial sectors categorized as high-risk industries, such as oleochemical manufacturing, are increasingly exposed to multiple hazards and safety-related challenges due to process complexity, the use of hazardous materials, and the critical role of human behavior. This research aims to examine the influence of safety communication on safety culture and operational excellence in high-risk industries within PT SCM, a leading oleochemical company in Indonesia. The objective of this study is to empirically determine the extent to which safety communication serves as a determinant in shaping safety-related behavior and enhancing organizational performance in high-risk plants. Utilizing a quantitative research design, data were gathered from 421 employees through structured questionnaires and subsequently analyzed using Structural Equation Modeling (SEM). The findings indicate that safety communication exerts a statistically significant impact on the internalization of safety culture (β = 0.724, p < 0.001) and contributes both directly (β = 0.368) and indirectly (β = 0.317) to the attainment of operational excellence. Furthermore, the analysis reveals that direct communication approaches, such as safety briefings, safety talks, and management walk-throughs, are more effective than symbolic or non-verbal modes. The study concludes that safety communication is not merely an administrative tool but a strategic organizational mechanism, essential for fostering employee engagement, reinforcing safe behavior, and sustaining high-performance outcomes within the organization.